Impacts of the gas atmosphere on the gasification reactivity and char structure of the brown coal - Wang, Y.; Sun, J.; Zhang, Shu (Zhongguo Meitan Xuehui, 2014)
Shengli brown coal was gasified at 800-900? in a simulated entrained-flow reactor to investigate the effects of steam, oxygen and their mixture atmospheres on the gasification characteristics. The impact mechanism of gasifying agents on the char structures and reactivity were systematically clarified using Fourier Transform Infrared Spectroscopy (FTIR) and thermogravimetric analyzer(TGA). The results indicate that the addition of oxygen to the gasifying agent (i.e. steam) is considered to able to optimize the gasification reaction and increase the H 2 yield, the largest increase valve of H 2 being 13% in this study. The -OH, -CH 3 and -CH 2 - functional groups drastically decrease during gasification. As a result, the regular structure of char and the aromatic degree increase. The reactivity of char from gasification in different atmospheres was evaluated by TGA, which shows the reactivity of char decrease with the increasing of the concentration of steam, and further addition of O 2 restrain the reactivity index of char, whose minimum value obtained is 0.005 min -1 . Under the oxygen atmosphere, the lower oxygen concentration demonstrates less influence on the reactivity of char.